Let Your Lawn Tell You When To Water - Laurie E. Trenholm; Joseph Bryan Unruh (EDIS, 2004)
Most homeowners over-water their lawns, which may damage or kill the lawn over time. Excess irrigation is one of the major causes of lawn demise and may include problems such as a shallow root system; increased disease, weed, or insect infestation; reduced drought tolerance; increased thatch and excessive growth; and reduced tolerance to other stresses such as shade and soil problems. To avoid over-watering, look for signs that the lawn needs water. This document is ENH63, one of a series of the Department of Environmental Horticulture, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Dates reviewed: March 2000; September 2003.